The Effect of Kecombrang (Etlingera elatior) Extract Addition on Characteristics of Kefir - Rifda Naufalin; Triana Setyawardani; Ridha Nur Fadhila Gunawan (ANIMAL PRODUCTION, 2024)
. This study aimed to investigate the characteristics of cow's milk kefir using different types of kecombrang extracts (leaves, flowers, and stems) and varying extract concentrations to identify the optimal combination of extract types and concentrations to achieve the highest antioxidant activity in kefir. A completely randomized design (CRD) was employed, factoring the kecombrang extracts (leaf, flower, and stem) and the concentrations (2.5%, 5%, and 7.5%). The kefir characteristic variables were analyzed using ANOVA, followed by Duncan's multiple range test at a significance level of α=5%. The results indicated that the type of kecombrang extract influenced viscosity, color value, antioxidant content, and sensory properties of taste and overall acceptability. Increasing the extract concentration enhanced the color value and viscosity. The optimal kefir formulation was achieved with the addition of 7.5% kecombrang flower extract that resulted in the highest antioxidant content of 74.83%. Cow's milk kefir incorporated with 7.5% kecombrang flower extract contained 90.6% water, 0.99% ash, 2.19% fat, 6.82% protein, and 0.6% carbohydrates, all of which comply with CODEX STAN 243-2003.